2020 5th IEEE International Conference on Recent Advances and Innovations in Engineering (ICRAIE) 2020
DOI: 10.1109/icraie51050.2020.9358301
|View full text |Cite
|
Sign up to set email alerts
|

Sentiment Analysis on COVID-19 Twitter Data

Abstract: Corona Virus or COVID-19 first appeared in December, 2019 in Wuhan, China. People tweeted aggressively on twitter at that time. This paper analysed the tweets regarding COVID-19 from November, 2019 to May, 2020 in India and its affect. All tweets are categorized into 3 categories(Positive, Negative and Neutral). Multiple datasets are created Statewise, Month-wise, combined of all states to analyze the people's reactions towards Lockdown in June, 2020 and about everything related to COVID-19. Most people starte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 2 publications
3
12
0
4
Order By: Relevance
“…Klasifikasi teks dari postingan media sosial [5], [6] selalu menjadi masalah penelitian yang menarik dan memiliki tantangan tertentu. Kajian analisis sentimen media sosial tentang COVID-19 menghasilkan lima tema relevan yang berkisar dari positif hingga negatif [7]- [11].…”
Section: Pendahuluanunclassified
“…Klasifikasi teks dari postingan media sosial [5], [6] selalu menjadi masalah penelitian yang menarik dan memiliki tantangan tertentu. Kajian analisis sentimen media sosial tentang COVID-19 menghasilkan lima tema relevan yang berkisar dari positif hingga negatif [7]- [11].…”
Section: Pendahuluanunclassified
“…Existing studies on COVID Twitter sentiment analysis (Manguri et al, 2020;Kaur and Sharma, 2020;Vijay et al, 2020;Chakraborty et al, 2020;Singh et al, 2021) mostly use TextBlob (Loria, 2018), or some simple supervised models (Machuca et al, 2021;Kaur et al, 2021;Mansoor et al, 2020).…”
Section: Classify Sentiments Towards Governorsmentioning
confidence: 99%
“…Kudchadkar et al [24] observed trends in concurrent #PedsICU and #COVID19 usage which reflect evolving information, knowledge gained, and collaborations among the global pediatric critical care community in Twitter. In terms of sentiment analysis, Vijay et al [25] analysed the tweets regarding COVID-19 from November 2019 to May 2020 in India and its effect. Most people started having Negative tweets but with increasing time shifted towards positive and neutral comments.…”
Section: B Content Analysis Reviewmentioning
confidence: 99%